Personal Characteristics and Adaptation Mechanisms of Patients with Arterial Hypertension and Chronic Heart Failure - E. V. Efremova; A. M. Shutov; E. V. Petrova (SINAPS LLC, 2021)
Adaptation processes in chronic diseases, including arterial hypertension (AH) and chronic heart failure (CHF), depend both on the personality of the patient and on comorbidity. Objective: to study the characteristics of adaptation and mental functioning of patients with hypertension and heart failure with comorbidity (the patient has concomitant diseases). Design and methods. 122 patients (49 women and 73 men, average age 62.9 ± 9.4 years) with hypertension and heart failure were examined. AH was diagnosed and evaluated according to guidelines for the treatment of arterial hypertension of the European Society of Hypertension and the European Society of Cardiology (2013). CHF was diagnosed in accordance with the guidelines for the diagnosis and treatment of chronic heart failure of the Society of Heart Failure Specialists, Russian Cardiology Society (2016). Charlson Comorbidity Index (IC) was used to evaluate comorbidity; comorbidity was regarded as high at IC ≥ 6 points (60 patients). To assess personal characteristics and mental status, a projective methodology was used - Sondi's test, a Mini-mult questionnaire (shortened version of MMPI). To assess the adaptive psychological mechanisms were used «Life Style Index» and «Copy Test». Cognitive functions and quality of life were evaluated. Results. IC was 5.3 (IQR:4-7) points. The group of patients with hypertension, heart failure and high comorbidity differed in the severity of the depressive-hypochondriacal profile compared with patients with low comorbidity. Similar data were obtained in a projective methodology: in the group with high comorbidity, the most pronounced factor is D− (depression) (1.7 (IQR: 1-2) and 0.9 (IQR: 0-1), points respectively, p = 0.009) and factor P− (paranoid) (1.8 (IQR: 1-2.5) and 1.3 (IQR: 1-2) points respectively, p= 0.01). Relationships have been identified that make it possible to talk about common adaptation processes in patients with AH and CHF depending on comorbidity: in patients with high comorbidity, non-constructive coping strategies («confrontational», «flight-avoidance») correlated with psychological defense mechanisms of the regression type (r=0.41, p=0.003) and replacement (r=0.39, p=0,001). Conclusions. Comorbidity has a negative impact on the cognitive and adaptive capabilities of patients with hypertension and heart failure, contributes to the emergence of depressive-hypochondriacal conditions, accompanied by a decrease in motivation and adherence to treatment, which must be taken into account with an interdisciplinary approach to this category of patients.